Uma descrição sistêmico-funcional do grupo verbal do português brasileiro orientada para os estudos da tradução - Arthur de Melo Sa (2016)
This research draws on systemic functional linguistics (HALLIDAY; MATTHIESSEN, 2014) to develop a translation studies oriented description of the Brazilian Portuguese verbal group(TOURY, 1995; MUNDAY, 2008; HALLIDAY; MCINTOSH; STREVENS, 1964; MATTHIESSEN, 2001). The verbal group is an important constituent of the clause in Brazilian Portuguese, and this research aims at describing it and demonstrating the appliability of the description to translation studies (HALLIDAY, 2009; MATTHIESSEN; TERUYA; WU,2008). Data were retrieved from Calibra (Catálogo da Língua Brasileira), a monolingual corpus organized according to systemic functional parameters (FIGUEREDO; PAGANO, 2012). Analysis was carried out in two steps: (i) first, a complete text of each subcorpus was examined in order to create models of both the verb and the verbal group; and (ii) secondly, corpus segments were randomly selected (accounting for approximately 5000 tokens) and analyzed to test the previously created model. Results were organized according to the trinocular perspective: "from below", the verb was described in terms of its composition: experiential morpheme, interpersonal morpheme and logical-semantic morpheme; "from roundabout", the verb was described in terms of the relations between morphemes and the paradigms that organize them in system networks, namely: VERBALITY, EXPERIENCE TYPE andTAXIS and LOGICAL-SEMANTIC relations between verb morphemes; and "from above", the verb was described in terms of the functions it realizes in the verbal group. Intersecting the view of the verb "from above" and of the group "from below" allowed for describing the verbal group according to its composition: Head, Event, Auxiliary, Modal, prepositions and conjunctions. "From roundabout" systems of the verbal group were described in a low degree of delicacy, namely: EVENT TYPE, INITENESS, SECONDARY TENSE, ASPECT, AGENCY, MODALITY and TAXISand LOGICAL-SEMANTIC RELATIONS between the verbal groups. Contributions of the verbal group to the clause were also observed "from above", more specifically: contributions for the realization of negotiation and experience, as well as clauses without a verbal group. Results arediscussed from a contrastive linguistics perspective, comparing Brazilian Portuguese and English verbal groups in order to discover potential formal correspondents (CATFORD, 1965; MATTHIESSEN, 2001) and develop a multilingual system (TEICH, 2001; MATTHIESSEN; TERUYA; WU, 2008) that accounts for the linguistic contact between those language systems. The study evidences a solid description of the Brazilian Portuguese verbal group and demonstrates its applicability to both compared linguistics and translation studies.